Carbon nanotubes from waste cooking palm oil as adsorbent materials for the adsorption of heavy metal ions - Suriani Abu Bakar (Tanjung Malim, 2021)
Carbon nanotubes from waste cooking palm oil as adsorbent materials for the adsorption of heavy metal ions by Suriani Abu Bakar